Colorectal carcinoma cells (Caco-2) secrete stroma-inducing growth factors in a stroma-oriented direction. - Wardelmann, E; Kiriakidis, S; Dreschers, S; Behrens, P; Heim, I; Krischler, J; Pfeifer, U; Wernert, N (2003)
Understanding of the mechanisms by which epithelial tumor cells induce their supportive stroma in carcinomas is of great general interest for the development of new therapeutic anticancer strategies. In the present study we investigated whether polarized colorectal carcinoma cells (Caco-2) release well-known stroma-inducing factors diffusely or specifically at the stroma-oriented cell pole. We demonstrate that Caco-2 cells secrete vascular endothelial growth factor, tumor necrosis factor alpha and platelet-derived growth factor preferentially towards a basolateral stroma-oriented direction. Other cytokines such as several interleukines, basic fibroblastic growth factor and prostaglandin E2 are not secreted in significant amounts by Caco 2 cells. We conclude that the directed secretion of stroma-regulating factors might play a central role in the regulation of both tumor angiogenesis and tumor invasion in carcinomas with a polarized growth pattern.